Fiber content evaluation and consumer preference of broiler chicken dim sum enriched with wood ear mushrooms - Annisa Yumna Fauzi; Ninna Rohmawati; Lirista Dyah Ayu Oktafiani (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2025)
Broiler chicken (Gallus domesticus) dim sum is a popular food known for its diverse composition and low fiber content. To increase fiber content, ear mushrooms (Auricularia sp.) were added to the dim sum. This study aimed to determine the fiber content, panelists' preference, and the appropriate portion of broiler dim sum as a side dish. The experimental study involved four treatment levels and six replicates with each sample weighing 20 g. This study was conducted in January, 2024. The fiber content test used an enzymatic method, whereas the preference test used a hedonic test assessed by 30 panelists. Data analysis was performed using the Friedman and Wilcoxon tests, as well as one-way ANOVA. The results showed an increase in fiber content, with the highest fiber content found in sample X3 at 2,43 grams. There were differences in color and texture (p<0,05), whereas there were no differences in taste and aroma (p>0,05). Sample X2 is the preferred sample. Therefore, the recommended portion of broiler chicken dim sum (X2) as a comfort food for men and women aged 19-29 years is two pieces. In conclusion, the addition of ear mushrooms can significantly increase the fiber content and preference of broiler chicken dim sums.